Scooby-doo! and you : the case of the haunted hound - Erwin, Vicki (New York : Scholastic, 2000)
Zowie! It's a haunted holiday when Fred wins a weekend for the Scooby gang at the mysterious bed and breakfast. In the middle of a storm, a giant dog appears and Scooby and Shaggy disappear!
"First Scholastic printing, November 2000."
Keywords: Detective and mystery stories; Children's stories